2017
DOI: 10.26630/jk.v8i2.410
|View full text |Cite
|
Sign up to set email alerts
|

Fraksi Kloroform Ekstrak Buah Mentimun (Cucumis sativus L.) Sebagai Anti Bakteri terhadap Staphylococcus epidermidis

Abstract: Chloroform Fraction of Extract Cucumber Fruit (Cucumis sativus L.) as of Antibacterial Staphylococcus epidermidis. The use of antibiotics in the community massively trigger resistance to bacteria, to that need for research on other alternatives, especially herbal medicine as an antibacterial. One of the medicinal plants are cucumbers that are widely available in Indonesia. The purpose of this study was to scientifically prove the antibacterial activity of chloroform fraction cucumber extract against Staphyloco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…Proses maserasi dilakukan selama 24 jam dengan pengadukan 6 jam sekali. Remaserasi dilakukan sebanyak tiga kali sampai diperoleh ekstrak yang kemudian akan diuapkan menggunakan evaporator dan oven dengan suhu 30 0 C sampai diperoleh ekstrak kental (Viogenta et al, 2017) .…”
Section: Ekstraksiunclassified
“…Proses maserasi dilakukan selama 24 jam dengan pengadukan 6 jam sekali. Remaserasi dilakukan sebanyak tiga kali sampai diperoleh ekstrak yang kemudian akan diuapkan menggunakan evaporator dan oven dengan suhu 30 0 C sampai diperoleh ekstrak kental (Viogenta et al, 2017) .…”
Section: Ekstraksiunclassified
“…One of the plants that has been proven to be efficacious as an acne medicine is cucumber (Cucumis sativus). Apart from being consumed by the public, cucumbers are also widely used to cure diseases, one of which is acne [5], previous studies have explained a lot about cucumber as an acne medicine, but there is still little research that discusses the benefits of the leaves. Phytochemical screening of cucumber leaf chloroform extract contains alkaloids, glycosides, steroids, flavonoids, saponins, and tannins [6], based on the results of the study, there were several phenolic compounds identified in cucumber leaves including cucurbit-asides B, cucurbit-asides C, and ferredoxin and also flavone glycosides such as isovitexin and saponarin which can act as antiinflammatory, anti-allergic, antimicrobial and antiviral.…”
Section: Introductionmentioning
confidence: 99%